DEMOGRAPHIC AND SOCIAL-CULTURAL DYNAMICS ON ACCESS TO SAFE SANITATION IN PASTORAL COMMUNITIES: A CASE OF SAKU SUB-COUNTY, MARSABIT, KENYA - Chichia, Marcus Labaru; Kirimi, Lilian Mukiri; Mberia, Jane Kawira; Eliud, Grace Kasiva (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
The Sustainable Development Goals (SDGs) aim for universal access to safely managed sanitation by 2030 and also emphasizes eradication of open defecation as a way to promote pathogen-free environment. Despite efforts to improve sanitation standards, significant challenges still persist, particularly in developing regions inhabited by pastoral communities and could be linked to unique components in the society. This study investigated the influence of demographic and social-cultural factors on access to safely managed sanitation in pastoral communities of Saku Sub-County, Kenya, where sanitation access is notably low. A cross-sectional descriptive design was employed. Semi-structured questionnaires were used to collect data from a sample of 100 household heads, calculated using Yamane’s adjusted formular. The data was analysed using Statistical Package for Social Sciences (SPSS) version 26 in descriptive and inferential statistics. Findings showed that gender roles were significant predictors of toilet adoption at the households (β=0.138, p=0.01). The nature of work for women such as having to look for water and for men like herding in lonely places where there were no toilets attracted open defecation cases. Latrine utilization was minimal at night due to safety concerns among females as indicated by 72% of the respondents. The cultural beliefs held in the region had a negative influence on toilet adoption (β=-0.130, p=0.040) while level of awareness on sanitation-related matters among the residents positively influenced adoption of safe toilets, thus increased access to safe sanitation (β=0.127, p=0.011). Construction of toilets near some households was undermined by the fear that the toilet pits would kill or injure livestock, which seemed to be given the highest priority. Traditions that revolved around restriction of latrine sharing between grown-ups and children attracted cases of open defecation even with access to toilets which suggested a need for toilets separation. The study recommended exploration of different context-appropriate mechanisms for triggering behaviour change to enhance sanitation standards among pastoral communities. An assessment of demographic characteristics, social and cultural practices prior to implementation of sanitation solutions, along with stakeholder involvement, could help in spotting any drawbacks towards ownership, uptake and sustainability of sanitation solutions.